Three-wavelength white electrophosphorescence with two emissive materials - Hsu, Shih-Feng; Laskar, Inamur R.; Chen, Teng-Ming; Hwang, Shiao-Wen; Chen, Chin H. (My University, 2005)
A New phosphorescent material based on Pt complex, Pt(btOMe)acac was synthesized and its specific EL emission spectrum from green to red combined with blue phosphorescent material. Firpic, can easily achieve high-efficiency three-wavelength white light with two emitters.